Follow‐up of the re‐evaluation of glycerol (E 422) as a food additive. (20th June 2022) - ,; Younes, Maged; Aquilina, Gabriele; Castle, Laurence; Engel, Karl‐Heinz; Fowler, Paul; Frutos Fernandez, Maria Jose; Gundert‐Remy, Ursula; Gürtler, Rainer; Husøy, Trine; Manco, Melania; Mennes, Wim; et al.
Abstract: Glycerol (E 422) was re‐evaluated in 2017 by the former EFSA Panel on Food Additives and Nutrient sources added to Food (ANS). As a follow‐up to that assessment, in this opinion, the Panel on Food Additives and Flavourings (FAF) addresses the data gaps identified to support an amendment of the EU specifications for E 422 in Commission Regulation (EU) No 231/2012. The Panel performed a risk assessment of undesirable impurities present in E 422. The Panel concluded that the maximum limits in the EU specifications for the four toxic elements (arsenic, lead, mercury and cadmium) should be lowered based on actual levels in the commercial food additive E 422. The Panel recommended setting a numerical limit value for acrolein in the specifications for E 422. The potential exposure to free 3‐monochloropropanediol at the maximum limit of 0.1 mg/kg, as laid out in the specifications for E 422, does not give rise to a health concern. The Panel recommended to consider modifying the definition of E 422 in Commission Regulation (EU) No 231/2012 indicating that E 422 is obtained only from vegetable oils and fats and undergoes purification processes that involve distillation, and other clean up steps to obtain refined glycerol. Overall, the Panel concluded that the technical data provided support an amendment of the specifications for glycerol (E 422).